Protein synthesis in the rumen: Ruminal urease inhibition by acetohydroxamic acid - Adepoju, A.; Portela, F.; Brent, B.E. (Kansas State University. Agricultural Experiment Station, 2011)
When urea is fed to ruminants, it is immediately converted to ammonia by an enzyme, urease. The ammonia usually becomes available faster than rumen bacteria can convert it to protein. Studies were reported last year (Bulletin 518) on attempts to slow down, or inhibit urease with acetohydroxamic acid. This year effects of acetohydroxamic acid on rumen ammonia, and volatile fatty acid levels in both sheep and cattle have been studied. In both, rumen ammonia was depressed for about 4 hours after feeding, and rumen fluid urea levels were increased, showing that urease was inhibited. Ammonia data for the steers showed no cumulative effect from prolonged use of acetohydroxamic acid, and no residual effect when it was withdrawn from the ration.
Keywords: Beef; Protein; Urease; Acetohydroxamic acid